Code-Mixing and Bilingualism in Indonesian Language Classrooms: A Case Study of Seventh-Grade Students in Riau - Sari, Lusi Komala; Nusen, Isfy Aprilian; Onwuagboke, Bede Blaise Chukwunyere (Actual Insight : Lembaga Penelitian Pengembangan, Penerbitan dan Publikasi, 2025)
This study explores the forms, functions, and social meanings of code-mixing and code-switching in a digital youth podcast broadcast on the TikTok platform. Adopting a descriptive qualitative approach and grounded in Grosjean’s critical sociolinguistic framework, the research analyzes the transcript of a conversational podcast episode featuring two Indonesian teenage girls discussing the topic of boyfriends versus best friends. The analysis reveals that code-mixing serves not only as a communicative strategy but also as an identity marker, a symbol of modernity, and a medium for expressing social solidarity among urban female youth. Conversely, code-switching is employed to mark topic shifts, emphasize emotions, and manage interpersonal dynamics during the podcast interaction. These bilingual practices reflect a process of glocalization, wherein youth flexibly mobilize multilingual resources within digital, media-rich contexts. The study underscores the pedagogical relevance of integrating authentic, digitally mediated discourse into language learning to enhance multilingual literacy and critical awareness. It also contributes to bilingualism studies by highlighting how identity and symbolic power are constructed through everyday linguistic practices in online spaces.